УЛС ТөРИйн СИСТеМ, наМЫн ХаРИЛцан ХаМааРаЛ: ОнОЛ-аРГа зҮй - Д.БОЛД-ЭРДЭНЭ; М.ДОЛЖИН (Politology, 2023)
The issue of political system and parties correlation has been an independent and biggest theory of political and studies methodology. Political science has been considering political system and parties correlation in the sphere of combined structure of such specific phenomena as political environment process, political system, parties system and political parties, but in their interdependency and distinction. The point is that political environment has been main sphere of parties activities, and the process of party”s forming in this sphere has been inseparable part of whole social political process, but partiesand their system have been a main structure of the whole social political system.